PERAN HUMANIST INSTITUTE FOR CO-OPERATION WITH DEVELOPING COUNTRIES (HIVOS) DALAM PENGADAAN ENERGI TERBARUKAN DI PULAU SUMBA TAHUN 2015-2018 - Zebua, Trisput Dt; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Sumba Island is one island in Indonesia that experiences limited energy services. The people of Sumba Island still rely heavily on the use of fossil fuels as an energy source. Despite the limitations of energy services, Sumba Island has considerable renewable energy potential that can be utilized as an energy source. Recognizing this, Hivos is driving the procurement of renewable energy on Sumba Island. Efforts to procure renewable energy services on Sumba Island are projected to be able to end the dependence of the Sumba community on fossil fuels and support community economic development. In 2010, Hivos initiated the Sumba Iconic Island (SII) program to procure renewable energy on Sumba Island. This research aims to determine the role of the Humanist Institute for Co-operation with Developing Countries (Hivos) in Procuring Renewable Energy on Sumba Island in 2015-2018. This research uses qualitative methods with document analysis techniques from books, journals, theses, reports, news and official documents from Hivos and the Sumba Iconic Island Program through the official website. Researchers used the perspective of pluralism and the theory of the role of non-governmental organizations. The results of this study indicate that Hivos plays a role in the procurement of renewable energy on Sumba Island by fulfilling the variables and indicators of the theory used. Hivos carries out its role through providers of goods, providers of works, capacity building, advocacy, campaigns, women empowerment, giving solutions, and cooperation carried out on Sumba Island in the 2015-2018 period. Keywords: Renewable energy, Hivos, Sumba Iconic Island.